Homeostasis of the body and implementation of the principle of unity between physical and technical training for high-level biathletes - Kryuchkov, A.S.; Dikunets, M.A.; Myakinchenko, E.B.; Missina, S.S. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the dynamics of biochemical blood parameters and kinematic parameters of simultaneous single-step skating in high-level biathletes. Methods and structure of the study. The proposed hypothesis was tested as part of a long-term comprehensive study involving biathletes who are members of the Russian national team. It was assumed that during the preparatory period, there is a correlation between the nature of training loads, the current condition of athletes, as assessed by blood biochemical markers, and the kinematic characteristics of simultaneous single-step skating. The informative value of all the indicators used has been substantiated in previous studies. Results and conclusions. Trends in changes in biochemical homeostasis were identified, reflecting the body’s stress response to loads and changes in the kinematics of skating. Different stages of the preparatory period are characterised by specific biochemical and kinematic adaptations, indicating the importance of optimal chronology of physical loads for effective improvement of running technique. A promising area of research is the study of neuromotor mechanisms of motor control, taking into account changes in biochemical homeostasis in athletes.